Conditioned courtship suppression in Drosophila melanogaster. (3rd July 2021) - Raun, Nicholas; Jones, Spencer; Kramer, Jamie M.
Abstract: Drosophila melanogaster males reduce courtship behaviour after mating failure. In the lab, such conditioned courtship suppression, aka 'courtship conditioning', serves as a complex learning and memory assay. Interestingly, variations in the courtship conditioning assay can establish different types of memory. Here, we review research investigating the underlying cellular and molecular mechanisms that allow male flies to form memories of previous mating failures.